2021
DOI: 10.3390/cancers13071714
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Oncological Biomarkers for Squamous Cell Cancer of the Head and Neck: Current State of the Art and Future Perspectives

Abstract: The era of immune checkpoint inhibitors has altered the therapeutic landscape in squamous cell cancer of the head and neck (SCCHN). Our knowledge about the tumor microenvironment has fueled the research in SCCHN, leading to several well-known and less-known prognostic and predictive biomarkers. The clinical staging, p16/HPV status, and PD-L1 expression are currently the main tools for assessing the patients’ diagnosis and prognosis. However, several novel biomarkers have been thoroughly investigated, some reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 189 publications
2
10
0
Order By: Relevance
“…While little is known about H. pittmaniae and its role in periodontal disease, the Haemophilus genus was identified in many positively classified studies per our LitSuggest text mining analysis. In a recent study by De Keukeleire et al (2021) a decrease in Haemophilus was associated with HNC-SCC, confirming findings by Wolf et al (2017) and Lim et al (2018) . However, studies by Guerrero-Preston et al (2016) and Gougousis et al (2021) found the opposite to be true.…”
Section: Discussionsupporting
confidence: 72%
“…While little is known about H. pittmaniae and its role in periodontal disease, the Haemophilus genus was identified in many positively classified studies per our LitSuggest text mining analysis. In a recent study by De Keukeleire et al (2021) a decrease in Haemophilus was associated with HNC-SCC, confirming findings by Wolf et al (2017) and Lim et al (2018) . However, studies by Guerrero-Preston et al (2016) and Gougousis et al (2021) found the opposite to be true.…”
Section: Discussionsupporting
confidence: 72%
“…In a review paper, the IL-6 serum level at diagnosis was significantly correlated to survival in 82/101 series comprising 9917 out of 11,583 patients with 23 different cancer types [ 24 ], including HNSCC [ 25 ] patients. We [ 26 , 27 ] and others [ 6 ] have also shown an association between monocyte tumor reactivity and HNSCC prognosis. We therefore aimed to study the level of macrophages as measured by CD68-positive cell infiltration in the studied OPSCC tumors in relation to long-term prognosis.…”
Section: Introductionmentioning
confidence: 82%
“…We have previously studied, in particular, oropharyngeal SCC (OPSCC), and therefore find it pertinent presently to use such patients. An advantage with this disease origin is that one may include investigation of different profiles between HPV-caused SCC versus OPSCC generated by tobacco and alcohol consumption [ 6 ]. These two different causes generate OPSCC with different tumor immune infiltration, histological malignancy degree and prognosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although HPV oncoproteins E5 and E6/E7 were supposed to activate the PD-1/PD-L1 axis ( 50 ), further research is required to elucidate the association between HPV oncoproteins and PD-L1. In addition, since PD-L1 gets up-regulated in response to tumor-infiltrating lymphocytes (TIL)-derived cytokines, the increase in PD-L1 expression in HPV-positive OPSCC might be related to a more inflamed tumor microenvironment with recruitment of TILs, rather than to a direct causative effect of HPV on PD-L1 expression ( 51 ). This theory is in line with the evidence that abundant TILs and high PD-L1 expression in intratumoral immune cells identified subgroups of HPV-positive OPSCC patients with excellent outcomes ( 27 ).…”
Section: Discussionmentioning
confidence: 99%